The Effect of Nutritional Status and Contact History toward Childhood Tuberculosis in Jember - Nurwitasari, Anasyia; Wahyuni, Chatarina Umbul (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTTuberculosis remains one of diseases with highest mortality among other. Indonesia had categorized in one of high burden countries since 2013. WHO estimated the annual global burden of childhood tuberculosis in 2012 was approximately530.000 cases and that up to 74.000 children died that year. The last three years tuberculosis incidence in Jember increased. In 2014, 6,5% of total tuberculosis incidence was childhood tuberculosis. Childhood tuberculosis is a major component in controlling tuberculosis. The objective of this study is to analyze determining factors of childhood tuberculosis incidence in Jember. This study is an analytical observational study using case-control design. The object of this study is children aged 0â14 years who diagnosed with tuberculosis in Jember Paru Hospital. Sampling taken by simple random sampling method. Sampel consisting 24 cases and 48 control. The independent variables is child nutritional status, contact history, long-term contact, and proximity contact. Analysis using Logistic Regression test to determine the influence between two variables. The results show that childhood tuberculosis incidence determined by contact history (p = 0,000; OR = 26,6), long-term contact (p = 0,000; OR = 69), and proximity contact (p = 0,000; OR = 27,1). The conclusion is, contact history, long-term contact, proximity contact determine childhood tuberculosis in Jember. Stakeholder have to do active case finding to break the chain of tuberculosis transmission with early household contact detection.Keywords: nutritional status, childhood tuberculosis, contact history, long-term contact, and proximity contact